DARI MASJID KE MEDIA: STRATEGI DAKWAH DIGITAL BERBASIS DATA DAN KONTEN KREATIF PEMUDA MUHAMMADIYAH JAWA TIMUR - Ahmad Shobrun Jamil; Khasna Shafwatul Jihan; Nabilatul Auliyana; Sumadi, Firasti Agung Nugrahening (Nusantara Hasana Journal, 2025)
Digital transformation in Islamic preaching (dakwah) has become an urgent necessity in the information disruption era. Pemuda Muhammadiyah of East Java, as an active religious youth organization, has strategic potential in utilizing information technology to expand its dakwah outreach. This community service program aimed to strengthen digital dakwah capacity through the development of an information system and training in digital content creation. The method used was a participatory qualitative approach involving the service team, PMM students, and Pemuda Muhammadiyah cadres. Activities included mosque data collection, data input into the pwpmjatim.org website, and the creation of video tutorials on data input and content editing using the Canva application. The results indicate that the program successfully increased cadre involvement in managing mosque information and producing digital dakwah content. Moreover, the mosque database system serves as a synergistic platform for data-driven dakwah. The program concludes that integrating information technology into community-based dakwah movements is essential, alongside expanding the coverage and ensuring program sustainability. Strengthening digital literacy among youth cadres is a crucial foundation for building an adaptive and competitive Muhammadiyah dakwah ecosystem.